A framework to interpret passively sampled indoor-air VOC concentrations in health studies. (15th August 2016) - Schlink, Uwe; Röder, Stefan; Kohajda, Tibor; Wissenbach, Dirk K.; Franck, Ulrich; Lehmann, Irina
Abstract: For an appropriate assessment of personal exposure in the indoor environment we suggest a framework for the utilization of VOC data measured by means of passive sampling. On the basis of 2246 measurements of 47 VOCs in flats in Leipzig, Germany, we explain how the concentrations have to be pre-processed for each VOC in order to come to a reliable assessment of the peak and cumulative exposures. Such adjustments are needed because of temporal variations in the concentration occurring due to season, renovation, application of dispersion paint and novel furnishing. For that purpose, robust conversion factors are derived with quantile regression. We also estimate the decay after renovation activities, e.g. for α-pinene the decay is (9.6 ± 3.7)% per month; the estimated half-life period for α-pinene is (7.2 ± 2.8) months, and (1.8 ± 0.4) months for dodecane. As a result of the pre-processing, an estimation of the peak concentration at renovation (at painting, and at arrangement of new furniture) and of the cumulative concentration is possible from a measurement taken at a later month. The suggested correction procedure may help avoid exposure misclassification in future epidemiological studies of the health effects of VOCs in indoor-air, from which novel results can be expected. Highlights: The time course of indoor VOCs is reconstructed when season as well as renovation activities are taken into account. The ratio between peak and measured concentration is larger for those compounds with larger seasonal amplitude. Those compounds that are released during renovation activities result in extra-large factors for the upper percentiles. Adjusted concentrations can strongly differ from raw VOC measurements.